Initiating exercise training early during the hospitalisation for an exacerbation of chronic obstructive pulmonary disease improves exercise capacity and quadriceps strength: A randomised controlled trial. (November 2020) - Mirza, Fatim Tahirah; Jenkins, Sue; Harrold, Megan; Othman, Siti Kamariah; Ismail, Rosmadi; Tengku Ismail, Tengku Saifudin; Hill, Kylie
Abstract: Background: Hospitalisations for an exacerbation of chronic obstructive pulmonary disease (COPD) impair exercise tolerance, muscle strength and participation in physical activity. Earlier studies of exercise training in this population often initiate training late in the admission and have not combined aerobic and resistance exercise. Objective: In adults hospitalised with an exacerbation of COPD, to determine the effects of aerobic and resistance exercise, initiated within 48 h of admission, on exercise tolerance, peak quadriceps muscle force (QMFpeak ), functional performance and physical activity. Methods: Thirty-eight patients (mean ± SD age 64 ± 7yr; FEV1 33 ± 14%pred) were randomised to a control group (CG; n = 18) or an exercise group (EG; n = 20). Both groups received usual care (airway clearance and encouragement to mobilise). Those in the EG participated in twice daily walking and resistance exercise. Outcome measures comprised the 2-min walk distance (2MWD), QMFpeak, performance on the Sit-To-Stand-Test (STST), Timed Up and Go (TUG) and physical activity measured using wearable technology. Results: Median [interquartile range] length of stay in the CG and EG were 7 [6 to 8] and 8 [6 to 9] days. Compared with the CG, those in the EG demonstrated greater gains in 2MWD (mean between-group difference; 95% confidence interval 13 m; 3 to 23) and QMFpeak (2.8 kg; 0.3 to 5.3). No between-group differences were seen in performance on the STST (1 repetition; −1 to 2), TUG (−0.8s; −0.2 to 0.4) and or daily steps (1462 steps; −469 to 3393). Conclusion: Exercise initiated early during a hospitalisation for exacerbation of COPD optimised exercise tolerance and QMFpeak . Clinical trial registration: This trial was prospectively registered with the Australian New Zealand Clinical Trials Registry; ACTRN12612000745842; URL: www.anzctr.org.au . Highlights: In people hospitalised for an exacerbation of chronic obstructive pulmonary disease; Exercise training initiated early during an admission was well tolerated. Improvements were noted in exercise tolerance and muscle strength. The exercise program increased the time spent walking at low intensity. Abstract : Hospitalisations for an exacerbation of COPD impair exercise tolerance and peripheral muscle strength. This randomised controlled trial demonstrated that a minimal-resource exercise program, initiated within 48 h of hospital admission for an exacerbation of COPD, was well tolerated and improved exercise tolerance and quadriceps strength when measured on discharge.